SUSTAINABLE VILLAGE DEVELOPMENT PLANNING: A CASE STUDY OF THE BI-SMART SOCIALIZATION PROGRAM IN NGEMPLAK SUBDISTRICT - Rozali Ilham; Aleknaek Martua (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2025)
This study aims to analyze the implementation of Bi-Smart socialization in Ngemplak District as an effort to design technology-based village development within the framework of the Sustainable Development Goals (SDGs). The main focus of the study is to evaluate the role of technology in improving the quality of public services, empowering village officials, and supporting the achievement of sustainable development goals at the village level. The research method used is a qualitative approach with a case study. Data were obtained through interviews with village officials, socialization participants, and relevant parties from the Boyolali Regency Communication and Informatics Office and the Yogyakarta Multimedia College (STMM). In addition, observations of socialization activities and documentation were conducted to gather information about technology implementation in village government. The results indicate that Bi-Smart socialization is effective in improving digital literacy among village officials and the community, accelerating access to information, and enhancing transparency and accountability in village administration. This program also opens opportunities for village economic development through the utilization of information and communication technology (ICT). However, challenges related to limited technological infrastructure and digital skills remain obstacles that need to be addressed. Overall, this study concludes that the implementation of SDG-based digital villages has significant potential to accelerate the achievement of sustainable development at the village level. Keywords: Digital Village, Bi-Smart, SDGs, Sustainable Development